Propagation of age‐related diseases due to the changes of lipid peroxide and antioxidant levels in elderly people: A narrative review. Issue 3 (23rd May 2022) - Ali, Julfikar; Aziz, Md. Abdul; Rashid, Md. Mamun Or; Basher, Mohammad Anwarul; Islam, Mohammad Safiqul
Abstract: Background and Aims: Lipid peroxidation end products are the major culprit for inducing chronic diseases in elderly people. Along with the elevated level of lipid peroxide biomarkers, there is a significant disruption of antioxidants balance, which combinedly propagate the diseases of elderly people. The aim of the present review is to bridge the connection of changes in lipid peroxides biomarkers and antioxidants level with age‐associated diseases in elderly people. Methods: This narrative review was performed following a comprehensive search for suitable articles in multiple online databases, including PubMed, Google Scholar, EMBASE, Web of Science, Cochrane Library, and ScienceDirect using selected search terms. The most appropriate literature was included based on the selection criteria. Results: From the review, it is found that many age‐related diseases propagated with an increased level of the end products of lipid peroxide and reduced levels of antioxidants in elderly people. When the end products of lipid peroxidation increase in the body, it creates oxidative stress, which ultimately leads to many complicated diseases, including cancers, cardiovascular and neurogenic diseases, and many other chronic inflammatory diseases. The oxidative stress induced by peroxidation can be assessed by different lipid peroxide end products such as malondialdehyde, oxidized low‐density lipoprotein, isoprostanes, neuroprostanes, lipoperoxides, oxysterols (7‐ketocholesterol, 7β‐hydroxycholesterol), and many more. Conclusions: This study definitively answers the correlation between the changes in lipid peroxides and antioxidants level and age‐related diseases. Our narrative article recommends future investigations for elucidating the mechanisms rigorously to establish a compact correlation.